DETERMINATION OF NITRITE AS 4-(4-NITROBENZENAZO)-1-AMINONAPHTHALENE DYE USING OPTICAL MEMBRANES BASED ON PVC-DOS MATRIX - Choirul Amri; Dwi Siswanta; Mudasir Mudasir (Indonesian Journal of Chemistry, 2005)
A study of a liquid polymeric membrane based on polyvinylchloride-dioctylsebacate (PVC-DOS) as optical membrane for the spectrophotometric and visual determination of nitrite has been done. The method relied on the formation of a purple colored 4-(4-nitrobenzenazo)-1-aminonaftalen dye in the membrane. The result showed that liquid polymeric membrane can be used as an optical membrane for the determination of nitrite. Optimum conditions of method achieved at a wavelength of 525 nm, reaction pH of 1.7-1.8, and respon time of 45 minutes. This method gave linear range of concentration at 0.0-0.17 mg/L NO2--N, detection limit of 0.004 mg/L NO2--N, and sensitivity of 4.981+0.110 absorbance unit per mg/L of NO2--N. The spectrophotometric and visual optical membrane method by is good for the determination of nitrite at the concentration range of 0.01-0.11 mg/L NO2--N and 0.02-0.60 mg/L NO2--N, respectively.